Protocol for a randomised controlled trial to improve cognitive functioning in older adults: the Iowa Healthy and Active Minds Study. Issue 2 (24th September 2011) - Wolinsky, Fredric D; Vander Weg, Mark W; Howren, M Bryant; Jones, Michael P; Martin, Rene; Luger, Tana M; Duff, Kevin; Goerdt, Christopher; Wolfe, Steven; Dotson, Megan M
Abstract : Objectives: Gradual age-related cognitive deteriorations are common and are hypothesised to be partially attributable to declines in information-processing speed. The Iowa Healthy and Active Minds Study will evaluate the efficacy and effectiveness of a computerised visual processing speed training programme ( Road Tour, Posit Science Corporation, San Francisco, California). Methods and analysis: Using a 3:3:4:4 ratio within two age strata (50–64 vs ≥65 years old), 681 men and women attending family care clinics were randomised to four treatment groups: 10 h of on-site Road Tour training, 10 h of on-site Road Tour training with 4 h of booster training at 11 months postrandomisation, 10 h of on-site attention control using computerised crossword puzzles ( Boatload of Crosswords, Boatload Puzzles, LLC, Yorktown Heights, New York) and 10 h of at-home Road Tour training using the participant's personal computer. The primary outcome, visual processing speed, was assessed at randomisation and post-training (6–8 weeks postrandomisation), and is being reassessed at 1-year postrandomisation using the Useful Field of View test. Five secondary outcomes (Symbol Digit Modalities Test, Trail Making Tests A and B, Controlled Oral Word Association Test, Digit Vigilance Test, and the Stroop Colour and Word Test) were assessed at randomisation and will be reassessed at 1-year postrandomisation. Seven hypotheses will be tested using intent-to-treat analyses involving multiple linear, logistic, Poisson and negative binomial regression. Ethics and dissemination: Ethics approval was provided by the University of Iowa Institutional Review Board (IRB-03 protocol 200908789). All participants completed signed informed consent prior to enrolment. Road Tour is commercially available from Posit Science Corporation, which provided it to Iowa Healthy and Active Minds Study at no cost. All participants will receive a free copy of Road Tour for unlimited perpetual use at study completion. Clinical Trial Registration Number: NCT01165463.